THE SOCIO-PHILOSOPHICAL CONTENT AND CONCEPTUAL INTERPRETATIONS OF THE INFORMATION SOCIETY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The emergence of the information society has become one of the most significant transformations of the twenty-first century, fundamentally reshaping social structures, economic systems, political institutions, and cultural values. The concept extends beyond technological innovation and encompasses profound changes in the organization of knowledge, communication, and social interaction. This article examines the socio-philosophical essence of the information society through an analysis of its conceptual foundations and theoretical interpretations. Employing comparative, historical-philosophical, and systems approaches, the study explores the evolution of the information society from industrial civilization to the digital era. The article critically examines the theoretical contributions of leading scholars, including Daniel Bell, Yoneji Masuda, Manuel Castells, Frank Webster, and Luciano Floridi, emphasizing their differing perspectives on information, knowledge, networks, and digital transformation. The study argues that the information society should be understood not merely as a technologically advanced stage of civilization but as a new socio-cultural paradigm characterized by the centrality of information, knowledge production, digital communication, and network governance. Furthermore, the article highlights the ethical, cultural, and philosophical challenges emerging from digitalization, including information inequality, identity transformation, artificial intelligence, and digital ethics. The findings demonstrate that the socio-philosophical interpretation of the information society requires an interdisciplinary approach integrating philosophy, sociology, political science, communication studies, and information science. Such an approach contributes to a deeper understanding of contemporary social transformations and provides a theoretical foundation for sustainable digital development.